2005
DOI: 10.1152/physiolgenomics.00076.2005
|View full text |Cite
|
Sign up to set email alerts
|

Digital transcriptome analysis indicates adaptive mechanisms in the heart of a hibernating mammal

Abstract: . Digital transcriptome analysis indicates adaptive mechanisms in the heart of a hibernating mammal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 38 publications
3
59
0
Order By: Relevance
“…Low heart rates and cardiac output generally lead to chamber dilation due to volume overload (Verduyn et al, 2001;Schoenmakers et al, 2003). These conditions in hibernators may have led to a noted variety of cardiac adaptations (Folk et al, 1970;Caprette and Senturia, 1984;Milsom et al, 1993;Milsom et al, 1999;Burlington and Darvish, 1998;Brauch et al, 2005). In humans, cardiovascular function ceases with a cessation of pacemaker conduction at about 20°C, and this acute failure masks more chronic failure of the heart where pumping function can be maintained at a lower temperature in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low heart rates and cardiac output generally lead to chamber dilation due to volume overload (Verduyn et al, 2001;Schoenmakers et al, 2003). These conditions in hibernators may have led to a noted variety of cardiac adaptations (Folk et al, 1970;Caprette and Senturia, 1984;Milsom et al, 1993;Milsom et al, 1999;Burlington and Darvish, 1998;Brauch et al, 2005). In humans, cardiovascular function ceases with a cessation of pacemaker conduction at about 20°C, and this acute failure masks more chronic failure of the heart where pumping function can be maintained at a lower temperature in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals transition from an active, euthermic state (37°C) to a hibernating state where torpid body temperature falls to 3-5°C but is punctuated repeatedly by arousals to euthermy. During bouts of torpor over a 6 month hibernation, these animals may be completely inactive for 2 weeks at a time at near-freezing temperatures, while arousals may last 24 h. Cardiovascular adaptations must occur for the myocardium to remain healthy and efficient during a period of extremely low temperatures, and low heart rate and cardiac output (Folk et al, 1970;Caprette and Senturia, 1984;Milsom et al, 1993;Milsom et al, 1999;Burlington and Darvish, 1998;Brauch et al, 2005). Non-hibernators that suffer from low heart rate conditions alone will develop cardiac chamber remodeling and congestive heart failure over time (Kertesz et al, 1997;Verduyn et al, 2001;Schoenmakers et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced mTORC1 phosphorylation during the entry stage could support an increase in the synthesis of selected proteins that are crucial to long-term survival in torpor. Indeed, previous studies on ground squirrel have identified a number of proteins that are selectively upregulated during torpor including, glucose-regulated protein 78, peroxisome proliferator-activated receptors- (PPAR-), PPAR- coactivator 1-, and peroxiredoxins (Prdx 1, 2 and 3) as well as enhanced expression of a variety genes, among them NADH-ubiquinone oxidoreductase subunit 2, myosin light chain 1 ventricular isoform, fatty acid binding proteins, adipophilin, mitochondrial uncoupling protein 2, pyruvate dehydrogenase kinase 4 and RNA binding motif protein 3 (Fahlman et al, 2000;Hittel and Storey, 2001;Storey and Storey, 2004;Eddy et al, 2005;Brauch et al, 2005;Mamady and Storey, 2006;Morin and Storey, 2008;Yan et al, 2007). These proteins are responsible for making crucial alterations that aid torpor survival, such as enhancing capacity for fatty acid metabolism and contributing to long-term cell preservation by elevating protein chaperones and antioxidant defenses.…”
Section: Thr1462mentioning
confidence: 99%
“…In contrast to single-gene expression analysis, the genome-wide approach also allows for identification of coordinated transcriptional changes in functional groups of regulatory genes within metabolic and signaling pathways. Recent studies of differential gene expression at the genomic scale on several species of hibernating small mammals have detected expression changes for hundreds of genes when comparing animals sampled in different stages during hibernation and nonhibernating periods (5,42,43,44). Coordinated transcriptional changes associated with hibernation have identified groups of co-regulated genes involved in carbohydrate, fatty acid and protein metabolism, detoxification, and molecular transport.…”
mentioning
confidence: 99%